2016
DOI: 10.13189/ujer.2016.040707
|View full text |Cite
|
Sign up to set email alerts
|

English Code Switching in Indonesian Language

Abstract: There is a growing phenomenon, worldwide, of inserting English words, phrases or expressions, into the local language: this is part of the acceptance of English as current world language. Indonesia is experiencing the use of this mixture of language when using either their own Indonesian or local language; English words, phrases and expressions are inserted into conversations and written expressions. The incorporation of foreign language words or expressions into a local language is conducted in a variety of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…When we trace back to previous studies on codeswitching, the researcher found much progress has been made in situating code-switching within a microsociological framework or that of ethnography of speaking, consistent with the goals of understanding the interactive purpose, communicative function, and social implications of this code alternation behavior, for instance, to name only a few, Setiawan [2]; Gumperz [3,4], Sankoff [5,6]; Denison [7]; Motschenbacher [8]; Marasigan [9]; Li [10]; and Widaya [11]. Similarly, a significant number of studies on codeswitching have focused directly on the linguistic aspects, especially syntactical or grammatical aspects of codeswitching, for instance, to name only a few, Hasselmo [12,13], Schiegg [14]; Gingras [15]; Amuzu [16]; Timm [17,18], and Mokgwathi and Webb [19].…”
Section: Introductionmentioning
confidence: 60%
“…When we trace back to previous studies on codeswitching, the researcher found much progress has been made in situating code-switching within a microsociological framework or that of ethnography of speaking, consistent with the goals of understanding the interactive purpose, communicative function, and social implications of this code alternation behavior, for instance, to name only a few, Setiawan [2]; Gumperz [3,4], Sankoff [5,6]; Denison [7]; Motschenbacher [8]; Marasigan [9]; Li [10]; and Widaya [11]. Similarly, a significant number of studies on codeswitching have focused directly on the linguistic aspects, especially syntactical or grammatical aspects of codeswitching, for instance, to name only a few, Hasselmo [12,13], Schiegg [14]; Gingras [15]; Amuzu [16]; Timm [17,18], and Mokgwathi and Webb [19].…”
Section: Introductionmentioning
confidence: 60%
“…Indeed, this is a reasonable answer because if the answer is the ability to preach in English is too high. Inserting English phrases into Indonesian language known as code switching is a prestige which is often done by high ranking officers in Indonesia when communicating in the public forum [19].…”
Section: Students' English Competencymentioning
confidence: 99%
“…John and Dumaniq (2013) studied code switching in Malaysian newspaper advertisements. Setiawan (2016) discussed the types of code switching in Indonesian contexts. Setiawan (2016) stated that Indonesian people were most likely to use code switching in a business relationship.…”
Section: Introductionmentioning
confidence: 99%
“…10, Desember 2019 P-ISSN 2301-5292 E-ISSN 2598-9995 Table 1. List of English Words in Business (Setiawan, 2016) Setiawan 2016stated that the words (in Table 1) were commonly discovered in a business context. Indonesian people were likely to borrow the terms and used the words when they spoke in Indonesian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation